(untitled) (American Journal of Islam and Society, 2006)
Scholars of state violence, among them sociologists and legal scholars, have insisted upon the existence of certain distinctions that separate those police methods deemed acceptable to the international human rights community from those methods of state brutality considered worthy of condemnation. Interestingly, most of the cases that cause confusion over what can be considered a legitimate use of state violence and what is condemned emanate from the same places: Serbia and Israel. James Ron’s impressive study of state violence under these two modern regimes offers an important genealogical and comparative analysis of these blurred moral, ethical, and analytical lines. Ron’s work in Frontiers and Ghettos highlights, in particular, patterns of state violence in territories that are under varying degrees of direct state control. These patterns both challenge assumptions about Israeli and Serbian history and serve as a corrective to much of the theoretical literature on state violence. Ron clearly argues that it is the nature of the state’s formal relationship with its territories that ultimately determines the level of state violence in both the Balkans and Palestine. His insight into these patterns is, perhaps, especially persuasive because they are fruitfully compared over distinct periods of both regions’ history. At the heart of this provocative study is a bravely argued claim that patterns of state violence vary because of international borders and how states operate within and beyond them. Ron suggests that geographical and administrative borders enforce a certain relational order between mechanisms of coercion and the extent to which the international community will tolerate state brutality. To make his argument, he carefully outlines how Serbian and Israeli repertoires of coercion dramatically changed depending upon the nature of each state’s direct relationship with the territories in which they operated. In the cases of Serbia’s activities in the former Yugoslavia and Israel’s actions in Palestine and southern Lebanon, he sees a pattern of ...